2023
DOI: 10.3390/metabo13050619
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effect of Dietary Gamma-Aminobutyric Acid (GABA) and Water Temperature on Growth Performance, Blood Plasma Indices, Heat Shock Proteins and GABAergic Gene Expression in Juvenile Olive Flounder Paralichthys olivaceus

Abstract: Gamma-aminobutyric acid (GABA) is an important inhibitory neurotransmitter in the central nervous system of living organisms and has the ability to reduce the magnitude of stress in humans and animals. In this study, we evaluated the supplemental effects of GABA on normal and high water temperature based on growth, blood plasma composition as well as heat shock proteins and GABA-related gene expression in juvenile olive flounder. For this, a 2 × 2 factorial design of experiment was employed to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
2
5
1
Order By: Relevance
“…As a result of the analysis of the current study, significantly higher SOD levels were obtained in the experimental groups to which GABA was added. It was found that GABA decreased oxidative stress and increased the activity of antioxidant enzymes in fish, as found in humans, rats, broilers, hens, and pigs, as well as similar to those found in fish and shellfish [15,[20][21][22][23][24][25][26][27][28][29]45]. The results of the present study indicate that dietary GABA can attenuate stress in fish due to high stocking density, which is in agreement with results found in the case of the antioxidant enzyme SOD in Roman hens exposed to heat stress [44], the glutathione (GSH) enzyme in largemouth bass fish exposed to ammonia stress and in turbot fed a high soybean meal diet [52,53].…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…As a result of the analysis of the current study, significantly higher SOD levels were obtained in the experimental groups to which GABA was added. It was found that GABA decreased oxidative stress and increased the activity of antioxidant enzymes in fish, as found in humans, rats, broilers, hens, and pigs, as well as similar to those found in fish and shellfish [15,[20][21][22][23][24][25][26][27][28][29]45]. The results of the present study indicate that dietary GABA can attenuate stress in fish due to high stocking density, which is in agreement with results found in the case of the antioxidant enzyme SOD in Roman hens exposed to heat stress [44], the glutathione (GSH) enzyme in largemouth bass fish exposed to ammonia stress and in turbot fed a high soybean meal diet [52,53].…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, GABA has been known to possess antidiabetic, antioxidant, and immune-modulating properties [ 35 ]. Due to the well-reported biological activities, GABA as a functional feed additive has been widely used in the animal industry to improve growth performance and to prevent heat stress-related signs in farm animals [ 36 ], fish, and shrimp [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The results of this experiment showed that dietary GABA did not reduce the stocking density stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations